OPTIMALISASI WAKAF PRODUKTIF: STUDI KOMPREHENSIF MODEL PENGEMBANGAN DAN TATA KELOLA BERKELANJUTAN DI INDONESIA - Assiddiq, Mahfuz; Supriadi; Kamaruddin (An Nuqud Journal of Islamic Economics, 2025)
This research aims to comprehensively analyze the concept, models of development, and sustainable governance of productive waqf in Indonesia. Using a qualitative approach through library research, data were obtained from books, scientific journals, regulations, and official reports related to productive waqf management. The findings show that productive waqf has significant potential as an economic and social empowerment instrument when managed professionally and sustainably. The main difference between productive and consumptive waqf lies in asset utilization, where productive waqf focuses on generating sustainable economic value through leasing, business ventures, and investment models. The study highlights the need for strong legal frameworks, competent nazir, and high public literacy to optimize productive waqf as a pillar of inclusive and competitive economic development in Indonesia.